De Novo Variants in the DYNC1H1 Gene Associated With Infantile Spasms - Yang, Haipo; Gong, Pan; Jiao, Xianru; Niu, Yue; Zhou, Qiujun; Zhang, Yuehua; Yang, Zhixian (Frontiers in Neurology, 2021)
Objective: The DYNC1H1 gene is related to a variety of diseases, including spinal muscular atrophy with lower extremity-predominant 1(SMA-LED1), Charcot-Marie-Tooth disease, type 2O (CMT2O) and mental retardation, autosomal dominant13 (MRD13). Some patients with DYNC1H1 variant also had epilepsy. This study aimed to detect DYNC1H1 variants in Chinese patients with infantile spasms (IS). Methods: We reviewed clinical information, video EEG, and neuroimaging of a newly identified cohort of five patients with de novo DYNC1H1gene variants. Results: Five patients with four DYNC1H1variants from four families were included. All patients had epileptic spasms (ES), the median age of seizure onset was 7.5 months (range from 5 months to 2 years and 7 months), and the interictal V-EEG results were hypsarrhythmia. Four out of five patients had brain MRI abnormalities. Four de novo DYNC1H1 variants were identified, including two novel variants (p.N1117K, p.M3405L) and two reported variants (p.R1962C, p.F1093S). As for the variant site, two variants are located in the tail domain, one variant is located in the motor domain, and one variant is located in the stalk domain. All patients had tried more than five kinds of antiepileptic drugs (AEDs). One patient has been controlled well by VGB for 4 years, another patient by VGB and steroids for 1.5 years. The other three patients still had frequent ES. All patients had severe intellectual disability and development delays. Significance: IS was one of the phenotypes of DYNC1H1 variants. Most patients had nonspecific brain MRI abnormality. Two out of four DYNC1H1 variants were novel, expanding the variant spectrum. The IS phenotype was related to the variant’s domains of DYNC1H1 variant sites. All patients were drug-refractory and showed development delays.